Development of a Quality Manual for ActivAsia, Inc. - Buera, Christian Arnold A.; Rañeses, Nestor (Quezon City Technology Management Center, University of the Philippines Diliman, 2011)
With the ever-increasing demand for more quality goods and services in a highly competitive global business environment, it is imperative for firms to be able to inject an organizational culture for excellence and emphasis on quality results. Laying down the foundation for a quality system is something that could spell survival for firms who are entrusted with managing marketing and promotion initiatives for clients with multi-million dollar market shares. This study focuses on the development of a formal quality manual for ActivAsia, Inc., an integrated channel activation marketing agency, providing high-level expertise to leading fast-moving consumer goods (FMCG) and retail companies in various channels. It is also the objective of this study to utilize the quality manual developed in this study as a basis for the formulation and implementation of a formal quality management system for ActivAsia, Inc. The Philippine National Standard, PNS ISO 9001 : 2008, Quality management systems-Requirements, which is the same as the International Standard ISO 9001 : 2008, was used as a framework for the development of the quality manual. Upon completion of the study, the quality manual should also serve as a master plan in the planning and crafting of the necessary documentation required for ActivAsia, Inc., and its plans for future ISO certification.
In partial fulfillment of the requirements in TM 299.2.
Thesis
Keywords: ActivAsia, Inc; Quality Manual; Quality assurance